Limb salvage with microvascular free fibula following primary bone sarcoma resection - Sahasrabudhe Parag; Panchwagh Yogesh; Jesal Rathod; Panse Nikhil; Jadhav Amit (Indian Journal of Plastic Surgery)
Background: Extremity sarcomas are challenging to manage. Total eradication of tumour has to be balanced with restoration of limb function to prevent mortality and morbidity. Disease-free survival with maximum limb function is the ultimate goal in these patients. Materials and Methods: We present a series of ten cases of extremity malignancies, where limb salvage was attempted with microvascular free fibula for limb reconstruction from the period of 2008 to 2015. Results: Of the ten cases in the study, there were two females and eight males. There were nine patients with lower limb malignancies and one patient with upper limb malignancy. There were four patients with Ewing’s sarcoma of femur, five patients with osteosarcoma of femur and one patient with chondrosarcoma of the humerus. The follow-up period ranged from 1.2 to 6.2 years with mean follow-up of 3.1 years. There were two deaths during follow-up, both were due to distant metastasis. The assessment of the function was done on the basis of Musculoskeletal Tumour Society functional score. Maximum score was 30 and minimum score was 24, the average score being 26. Of the eight surviving patients, three patients had full weightbearing, four patients had partial weightbearing at end of 2 years and one patient of upper limb reconstruction had complete upper limb function. None of the patients had to undergo limb amputation. Conclusion: Limb salvage with vascularised fibula graft offers good functional outcome along with good disease-free survival rates.